THE EFFECT OF USING THE DUOLINGO APPLICATION AS A MEDIUM IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Tarisa Azzahara; A. Muliati; Geminastiti Sakkir (Universitas Negeri Makassar, 2023)
The purpose of this study was to determine whether using the Duolingo app significantly improved students' vocabulary mastery skills. This study was carried out at SMP Negeri 1 Sungguminasa. This research took place at SMP Negeri 1 Sungguminasa. The population of. This research was the students of SMP Negeri 1 Sungguminasa. The sample of this research is 35 students. The researcher used a quantitative technique. The instrument of this research was a vocabulary test which was administered as a pre-test and post-test. Based on the result of the mean score, the researcher found that the effect of Duolingo Application can improve student’s vocabulary mastery. It was proved by the result of the post-test which was higher than the result of the pre-test (76.74 > 50.31). The value of the t-test is more significant (0.005). Then, the researcher concludes that the use of the Duolingo application was effective in improving the students’ vocabulary mastery.